Percepção ambiental em uma comunidade evangélica: a contribuição da igreja presbiteriana Betânia de Piratininga para a conscientização ambiental - Esteves, Ricardo dos Santos (2009)
This study is intended to verify the level of environmental conscientiousness of the members of a Presbyterian Betânia Church, located in the neighborhood of Piratininga, in the Oceanic region of the city of Niterói. The work is aimed on the analysis of the environmental and philosophical contents of the gospel and the religious teaching of the shepherds. Besides. During August 2004 and February 2005, the author applied 50 questionnaires to a group of 50 members of the church and specific questionnaires to the three shepherds of the community. Further 50 questionaires were applied to a control community that never participated of the Presbyterian Church. The interviews of the members of the church, of the shepherds and of the non members were compared and the interpretation of the results indicates that the biblical texts are not an explicit aim of the shepherds gospels to transmit an environmental message. Therefore, it was suggested that some modifications on the transmission of the biblical doctrine would be profitable, which would be carried out through the Sunday s Biblical School and other events within the church. This work opens excellent perspectives for the insertion of an environmental conscientiousness for the poor evangelic communities in Brazil.